Peningkatan Hasil Belajar dan Sikap Ilmiah Peserta Didik pada Materi Genetika melalui Model Cooperative Learning Tipe Peer Tutoring - M. Zainuddin; Sri Wardhani; Saleh Hidayat (BIOEDUSAINS:Jurnal Pendidikan Biologi dan Sains, 2023)
This study aims to improve the learning outcomes and scientific attitudes of class XII students of MAN Cendekiawan OKI by using the Peer Tutoring Type Cooperative Learning model through Classroom Action Research which includes the stages of planning, implementing, observing and reflecting. This research method is quantitative. The data obtained will be analyzed using the SPSS calculation application. The results showed that there was an increase in student learning outcomes and scientific attitudes, where at the end of the cycle the learning outcomes in the knowledge domain reached 95.8% (average score 89.17) and students' scientific attitudes also experienced an increase in indicators. Honest attitude is 3.84 (very good), 3.83 (very good) for cooperation and 3.77 (very good) for self-confidence. In conclusion, the application of the Peer Tutoring Type Cooperative Learning model can improve learning outcomes and scientific attitudes of class XII students of MAN Cendekiawan OKI. Keywords: Learning Outcomes, Peer Tutoring Cooperative Learning Model, Scientific Attitude